2020
DOI: 10.3390/nu12092828
|View full text |Cite
|
Sign up to set email alerts
|

Obese Adipose Tissue Secretion Induces Inflammation in Preadipocytes: Role of Toll-Like Receptor-4

Abstract: In obesity, the dysfunctional adipose tissue (AT) releases increased levels of proinflammatory adipokines such as TNFα, IL-6, and IL-1β and free fatty acids (FFAs), characterizing a chronic, low-grade inflammation. Whilst FFAs and proinflammatory adipokines are known to elicit an inflammatory response within AT, their relative influence upon preadipocytes, the precursors of mature adipocytes, is yet to be determined. Our results demonstrated that the conditioned medium (CM) derived from obese AT was rich in FF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 52 publications
(74 reference statements)
0
12
0
Order By: Relevance
“…Finally, in obese subjects, the adipocytes from VAT and SAT also express several molecules, such as lipocalin-2 [321,322], tenascin C, toll-like receptor 4 [323], and protein pentraxin 3 (PTX3) [324], which are related to adipose tissue inflammation and secretion of pro-inflammatory cytokines [321][322][323][325][326][327][328][329][330], insulin resistance [325,331], hyperglycemia and glucose intolerance [325,[332][333][334], endothelial dysfunction with hypertension [335], cardiovascular dysfunctions [336,337], and atherosclerosis [338,339].…”
Section: Visceral Abdominal and Subcutaneous Adipose Tissuesmentioning
confidence: 99%
“…Finally, in obese subjects, the adipocytes from VAT and SAT also express several molecules, such as lipocalin-2 [321,322], tenascin C, toll-like receptor 4 [323], and protein pentraxin 3 (PTX3) [324], which are related to adipose tissue inflammation and secretion of pro-inflammatory cytokines [321][322][323][325][326][327][328][329][330], insulin resistance [325,331], hyperglycemia and glucose intolerance [325,[332][333][334], endothelial dysfunction with hypertension [335], cardiovascular dysfunctions [336,337], and atherosclerosis [338,339].…”
Section: Visceral Abdominal and Subcutaneous Adipose Tissuesmentioning
confidence: 99%
“…While the signals emanating from adipose tissue to recruit the ASC pool for differentiation remain unresolved, current evidence demonstrates that adipose expansion is associated with a shift in the adipose secretome towards higher release of pro-inflammatory mediators [ 46 48 ]. Interestingly, a recent study showed an increase in differentiation of ASC exposed to the secretome of adipose explants from high fat-fed mice [ 46 ]. Adipocyte-specific dominant-negative mutation of the pro-inflammatory cytokine, TNFα, prevented diet-induced WAT expansion, demonstrating that adipocyte inflammation is required for adaptive WAT remodeling [ 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, animals lacking TLR4 were protected against insulin resistance generated by a high-fat diet [ 204 ]. In an ex vivo study, Renovato-Martins et al [ 205 ] demonstrated that the conditioned medium derived from obese adipose tissue induces inflammation in preadipocytes via increased TLR4 signaling and ROS production, thereby creating a paracrine loop that promotes the differentiation of preadipocytes into adipocytes with a proinflammatory profile. High levels of circulating free fatty acids (FFAs) are associated with obesity and have been demonstrated to induce insulin resistance via many proinflammatory pathways [ 174 , 206 , 207 , 208 ].…”
Section: Microbiome Dysbiosis At the Intersection Of Obesity And Glau...mentioning
confidence: 99%